Viewpoint From Computational Thinking to Computational Action: Envisioning computing education that both teaches and empowers. - Tissenbaum, Mike; Sheldon, Josh; Abelson, Hal (Communications of the ACM, 2019)
The article discusses the use of computational action as a framework for computing education in order for students to both learn about computing, through computational thinking, and create with computing. Topics include the use of computational action to make computing education more inclusive, motivating, and empowering for students, the two dimensions of computational action which are computational identity and digital empowerment, and the application of computing skills in problem-based learning.